Global Islamophobia and the rise of populism - Aziz, Sahar F.; Esposito, John L. (New York, USA : Oxford University Press, 2024)
"Islamophobia is a rapidly growing problem across the world arising from a convergence of right-wing populism, xenophobia, and a normalization of anti-Muslim scapegoating. The consequences are devastating for Uyghurs in China indefinitely detained in concentration camps, Indian Muslims attacked in pogroms, and the Rohingya murdered in a genocide. Muslims in the global north, meanwhile, are denied religious freedom and other civil rights on account of their purported corruption of liberal values. The case studies of ten countries across three continents-North America, Europe, and Asia-demonstrate a troubling trend: right-wing politicians, buttressed by civil society groups and conservative media outlets, deploy Islamophobia to intensify the majority ethnic populations' fears of losing power and wealth. Global Islamophobia in an Era of Populism is the first to tackle these complex, interconnected phenomena through empirically supported analysis by internationally known scholars"--
Includes bibliographical references and index.
Keywords: Islamophobia; Political Science; Nationalism; Islam; Populism